Blocking bad. (21st October 2015) - Scherer, Steven S.
Abstract : This scientific commentary refers to 'Targeting the colony stimulating factor 1 receptor alleviates two forms of Charcot–Marie–Tooth disease in mice', by Klein et al. (doi:10.1093/brain/awv240 ).